The Law on transfer and business taxation : with illustrations, problems, and solutions - De Leon, Hector S.; Hector M. De Leon Jr. (Manila, Philippines : Rex Book Store, 2013)
Taxation is the process or means by which the sovereign, through its law-making body raises income to defray the necessary expenses of government.
1. Estate tax -- 2. Gross state -- 3. Exclusions and exemptions -- 4. Deductions -- 5. Valuation -- 6. Schedule and computation of the tax -- 7. Basic concepts of succession -- 8. Notice of death and filing of return -- 9. Payment and sanctions -- 10. Donors tax -- 11. Business Taxation -- 12. --Value added Tax -- 13. Importation of goods -- 14. Other percentage taxes --15. Excise taxes on certain goods -- 16. Statutory offenses and penalties -- 17. Compliance requirements -- 18. Local Taxation -- 19.M.Real Property Taxes -- 20. Appraisal and Assessment of Real Property -- 21. Appeal on assessment, -- 22. Imposition of the tax -- 23. Special Levies on Real Property -- 24. Collection of the tax -- 25. Disposition of proceeds -- 26. Special provisions.
Keywords: BUSINESS ENTERPRISES